2014
DOI: 10.1021/jp500627z
|View full text |Cite
|
Sign up to set email alerts
|

pH Oscillations and Mechanistic Analysis in the Hydrogen Peroxide–Sulfite–Thiourea Reaction System

Abstract: A new pH oscillator has been constructed by combining the pH clock reaction H2O2-SO3(2-)-H(+) with thiourea (Tu, (NH2)2CS) as a proton-consuming species. The system exhibited oligo-oscillatory behavior in a closed system, and large amplitude oscillations in a continuous-flow stirred tank reactor (CSTR) were observed in a narrow range of input concentrations, flow rate, and temperature. For the purpose of constructing the kinetic model, a reversed-phase ion-pair high-performance liquid chromatography (HPLC) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
(56 reference statements)
1
3
0
Order By: Relevance
“…Formation of those species would lead to an absorbance decrease rather than the rise shown in Figure . The HPLC chromatogram of the product mixture (Figure S4) clearly reveals the formation of thiourea monoxide (TUO, (NH 2 ) 2 CSO) by comparing the retention time with that reported in literature; moreover, the UV spectrum of this species obtained by HPLC with diode-array detection corresponds to the spectrum of the product mixture (Figure S5). Figure S5a also shows that TUO has an absorbance maximum at 260 nm and a significant but smaller absorbance at 292 nm.…”
Section: Resultssupporting
confidence: 61%
“…Formation of those species would lead to an absorbance decrease rather than the rise shown in Figure . The HPLC chromatogram of the product mixture (Figure S4) clearly reveals the formation of thiourea monoxide (TUO, (NH 2 ) 2 CSO) by comparing the retention time with that reported in literature; moreover, the UV spectrum of this species obtained by HPLC with diode-array detection corresponds to the spectrum of the product mixture (Figure S5). Figure S5a also shows that TUO has an absorbance maximum at 260 nm and a significant but smaller absorbance at 292 nm.…”
Section: Resultssupporting
confidence: 61%
“…Thiourea dioxide ((NH 2 ) 2 CSO 2 , TDO) has been extensively used in chemistry and chemical technology as an effective reducing agent despite the fact that its transformation in redox reactions is not yet fully understood. Even nowadays new applications of this versatile compound have been reported that span a wide range of different areas in chemistry and chemical technology. Without providing an exhaustive survey the following important fields should be emphasized to support this statement: reduction of graphene and graphite oxides, preparation of nanometer-sized metal powders, organocatalysis, , polymerization reactions, and even in demonstrating nonlinear dynamical phenomena in chemical kinetics. , Majority of these new fields usually exploits rich chemistry of TDO such as its unusual structure, rearrangement in aqueous solutions, as well as its complex decomposition in different solvents. Focusing on the application of TDO in aqueous solution it is well-known that strong reducing feature of TDO in alkaline condition stems from a controlled release of sulfoxylic acid or sulfoxylate ion by splitting the unusually long C–S bond of the target molecule .…”
Section: Introductionmentioning
confidence: 99%
“…Without providing an exhaustive survey the following important fields should be emphasized to support this statement: reduction of graphene 4 and graphite oxides, 5 preparation of nanometer-sized metal powders, 6 organocatalysis, 7,8 polymerization reactions, 9 and even in demonstrating nonlinear dynamical phenomena in chemical kinetics. 10,11 Majority of these new fields usually exploits rich chemistry of TDO such as its unusual structure, rearrangement in aqueous solutions, as well as its complex decomposition in different solvents. Focusing on the application of TDO in aqueous solution it is well-known that strong reducing feature of TDO in alkaline condition stems from a controlled release of sulfoxylic acid or sulfoxylate ion by splitting the unusually long C−S bond of the target molecule.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The master system was the bromate–sulfite pH oscillator and the slave system was the hydrogen peroxide–sulfite pH oscillator (Figure ). , Both chemical systems have been intensively studied in the literature, and several nonlinear behaviors have been discovered and observed in these systems (e.g., bistability, bifurcation). In experiments, we used the following reagent-grade chemicals, NaBrO 3 (Sigma-Aldrich), Na 2 SO 3 (Sigma-Aldrich), H 2 SO 4 (Sigma-Aldrich), NaHCO 3 (Sigma-Aldrich), and H 2 O 2 (Sigma-Aldrich). The aqueous solutions of all chemicals were always prepared freshly before the experiments to avoid any decay of chemicals and the oxidation of sulfite.…”
Section: Experimental Sectionmentioning
confidence: 99%